Prolonged Thrombin Time in Asymptomatic Patient with Hypo Dysfibrogememia Tucson - Suresh, B Katakkar (Journal of Hematology and Oncology Research, 2021)
A 61 years female patient with known diagnosis of the breast cancer in remission for more than 10 years has Renaud’s disease. During her work up for lupus and lupus anticoagulant which both were negative a prolonged thrombin time was noted which was done by mistake. She has no history of bleeding or thrombosis and last recent surgery was 5 years ago for spinal stenosis and was uncomplicated. Her clinical examination is normal without evidence of any spontaneous bruises but colder hands. The thrombin time was greater than 125 seconds on two different occasions and correction of it by addition of normal plasma was down to 56 seconds and was thus incomplete. Her prothrombin time and PTT were normal and there was no evidence of FDP or D-Dimers. There was no evidence of circulating heparins. The fibrinogen level was normal. The para proteinmia was excluded by normal serum protein electrophoresis and by immunofixation . Thus it is felt that this patient has dysfibrinogenemia or hypo dysfibrinogenemia without bleeding or thrombotic complication. The literature review shows approximately 55% of dysfibrinogenemia patients do not have bleeding or thrombotic complications.
Keywords: Diagnosis; breast cancer; Thrombosis